"... der Augenblick ist mein und nehm ich den in Acht" Daseinsthemen und Lebenskontexte alter Menschen - Kruse, Andreas; Schmitt, Eric (Heidelberg University Publishing (heiUP), 2022)
Themes of existence of elderly people are considered in the context of different: different social classes, different residential contexts, different degrees of independence are understood as central components of the differentiated life-worlds. It is shown how significant the subjectively experienced "task character of life" as well as the experience of being needed by others are for satisfaction and a sense of meaning. In addition, risk factors for life satisfaction are identified: these include, above all, isolation and a pronounced need for care. The experience of old people is not solely determined by vulnerability; it also speaks for mental growth and coping skills.